Implementasi analisis SWOT dalam meningkatkan mutu pendidikan di Sekolah Menengah Pertama Islam Terpadu (SMP IT) Al Marwat Lemahabang - Mochamad Asep Kuswara; Gizka Amalia Putri (Universitas Negeri Padang, 2025)
Student Management in schools is able to foster the character of disciplinary values. Student Management is planned and carried out deliberately as well as gradual development of all students so that they can participate in the teaching and learning process effectively and efficiently. The character of discipline is an attitude that students must have to make learning run smoothly. This research uses descriptive qualitative research methods with data collection techniques, namely: observation, interviews and documentation. This research is able to make an important contribution to the implementation of discipline in schools by implementing student management. The implementation of student management has been proven to be able to foster the character of disciplinary values if carried out correctly and appropriately by educational institutions.